2015
DOI: 10.1111/eos.12230
|View full text |Cite
|
Sign up to set email alerts
|

Does prenatal restraint stress change the craniofacial growth pattern of rat offspring?

Abstract: A major and frequently encountered condition underlying the long-term programming effects of the intrauterine environment is exposure to stress. Gestational stress is an environmental factor that induces physical and behavioral alterations in offspring. Seventy female virgin Wistar rats were mated with one male rat for a maximum of four times, after which 52 pregnant rats were divided into two groups. In the experimental group the rats were exposed to restraint stress during pregnancy, whereas the control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…This is de--picted in one study in which re--straint stress was applied to a group of pregnant rat study mod--els to determine the extent of any changes in craniofacial growth patterns in rat offspring that in--trauterine stresses elicited [10]. The prenatally stressed group ex--perienced increases in anterior cranial base length and viscer--ocranium measures with back--ward rotation of the midface and decreased flattening of the cranial vault.…”
Section: Resultsmentioning
confidence: 99%
“…This is de--picted in one study in which re--straint stress was applied to a group of pregnant rat study mod--els to determine the extent of any changes in craniofacial growth patterns in rat offspring that in--trauterine stresses elicited [10]. The prenatally stressed group ex--perienced increases in anterior cranial base length and viscer--ocranium measures with back--ward rotation of the midface and decreased flattening of the cranial vault.…”
Section: Resultsmentioning
confidence: 99%
“…We found that although mean litter sizes and weights of all F 1 groups exposed to low temperatures were significantly reduced compared to the control group, infant mortality was highest in the progeny of combined preand post-natally stressed F1 females, indicating a greater reaction to longer term low temperature stress. Moreover, gestational stress, including exposure to teratogenic substances and extreme temperatures, has been shown to have adverse consequences on physical development, physiology, and behavior of rodents in other studies (Aminabadi et al, 2016;Benderlioglu et al, 2006;Breno et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The data were evaluated by the Kolmogorov-Smirnov test and Q-Q plot to check the normal distribution of data. Levene’s test was used to assess the equality of variances (20,21). Spearman’s correlations coefficient, Wilcoxon signed-rank and paired samples t tests were used for evaluation of relationships between quantitative variables.…”
Section: Methodsmentioning
confidence: 99%